Development of Learning Activities Based on 5 STEPs Collaborative Learning Process (CO-5STEPs) to Enhance Scientific Concepts and Teamwork for Grade 5 - Maiwong, Namfon; Kaewurai, Wareerat (Journal of Buddhist Education and Research (JBER), 2025)
This research was a development research (R&D) with two objectives: 1) create and evaluate the efficiency of learning activities based on 5 STEPs Collaborative Learning Process (CO-5STEPs) to Enhance Scientific Concepts and Teamwork for Grade 5, following the 75/75 efficiency criteria; 2) investigate the results of learning activities based on 5 STEPs Collaborative Learning Process (CO-5STEPs) to Enhance Scientific Concepts and Teamwork for Grade 5, 2.1) Compare the students’ scientific concepts before and after using 5 STEPs Collaborative Learning Process (CO-5STEPs), 2.2) Compare students’ teamwork after 5 STEPs Collaborative Learning Process (CO-5STEPs) to Enhance Scientific Concepts and Teamwork for Grade 5 to the 75/75 efficiency criteria. The sample consisted of 21 fifth-grade students of Ban Pakapi School, Uttaradit Province, academic year 2024, selected by purposive sampling. The instruments used were CO-5STEPs learning activities, CO-5STEPs learning plan, science concept test, and 4) teamwork assessment. The statistics used in data analysis included means, standard deviations, a T-test dependent, and a one-sample T-test. The results suggested that: 1)CO-5STEPs learning activities have the following steps: 1) Stimulating and Key Questioning Collaboratively, 2) Searching and Analyzing Collaboratively, 3) Discussing and Constructing Collaboratively, 4) Communicating and Reflecting Collaboratively, and 5) Applying and Serving Collaboratively. The appropriateness was at the highest level (x̄ = 4.88, = 0.21). The efficiency was 87.69/82.22, which is higher than the specified criteria. 2) Results of learning activities based on 5 STEPs Collaborative Learning Process (CO-5STEPs) to Enhance Scientific Concepts and Teamwork for Grade 5 were recommended as follows: 2.1) The scientific concepts after applying CO-5STEPs learning activities were significantly higher than before class at a statistical level of .05. 2.2) Related to teamwork, after teaching with CO-5STEPs learning activities were significantly higher than the specified criteria, 75 percent, at a statistical level of .05.